The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.34172/ajmb.2020.14
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antioxidant and Antimicrobial Activities of Silver Nanoparticles Biosynthesized by Haplophyllum Obtusifolium

Abstract: Background: Plants comprise great antioxidant sources as a result of their redox and biochemical components, which are rich in secondary metabolites such as phenolic acids, flavonoids, and other constituents. Haplophyllum obtusifolium from polygonaceae is widely used for preventing and managing diabetes. This study investigated the antibacterial and antioxidant activities of silver nanoparticles (AgNPs) biosynthesized by H. obtusifolium. Methods: The aerial parts of H. obtusifolium were gathered from the north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…[25][26][27][28] Thus, medicinal plants are widely under study because of their antioxidant materials and nutrient preservatives. [29][30][31][32] Bio-indicators can now be used to characterize toxicity or cancer. 33,34 Many studies have shown that nanotechnology provides a good alternative for cancer treatment.…”
mentioning
confidence: 99%
“…[25][26][27][28] Thus, medicinal plants are widely under study because of their antioxidant materials and nutrient preservatives. [29][30][31][32] Bio-indicators can now be used to characterize toxicity or cancer. 33,34 Many studies have shown that nanotechnology provides a good alternative for cancer treatment.…”
mentioning
confidence: 99%